Evaluation of relative permeabilities and excess enthalpy modeling for geothermal reservoirs - Felix Carl Sandström 1992- (2021)
Most geothermal systems in Iceland and worldwide used for power generation can be classified as liquid-dominated geothermal systems, meaning that the pressure-controlling phase is liquid. Boiling results as heated fluid ascends and the pressure decreases to saturation pressure. In most geothermal wells drilled into these systems, the enthalpy of the fluid produced from wells is approximately equal to the enthalpy of saturated liquid at the reservoir condition. However, in many of the wells, the measured discharge enthalpy is much higher than the enthalpy of single-phase liquid and can even approach the enthalpy of single-phase vapor. The higher specific enthalpy of such ‘excess-enthalpy’ wells results from phase segregation and, to a lesser extent, additional boiling in the fractures caused by conductive heat transfer. A better understanding of the phase segregation process is essential to improving the accuracy and utility of geothermal reservoir models and making more realistic estimates of the power generation potential of high-enthalpy geothermal resources. Relative permeability is a measure that quantifies interactions between the flowing phases and the rock and strongly influences phase segregation behavior. They can be expressed as functions of the static liquid saturation and are used in reservoir models to simulate multiphase flow. Based on well data from two geothermal fields in Iceland, Nesjavellir and Hellisheidi, relative permeabilities were calculated, and curves were estimated for several wells using the Shinohara method (Shinohara, 1978). By using models of fluid flow towards a producing wellbore, one objective of the thesis was to see how these curves affected the discharge enthalpy. Two types of radial models were created and tested: 1) a single porosity (SP) model and 2) a multiple interacting continua (MINC) model. The SP models, which has uniform permeability and porosity, could not generate discharge enthalpies above 2000 kJ/kg. The MINC models, however, involving both matrix and fracture ...